ECOLOGICAL MONITORING ON THE BASIS ARCGIS GEOGINFORMATION PLATFORM - Fedchenko, O.; Kulynych, I.; Storubliov, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2020)
Ever-changing parameters of the Earth’s atmosphere and environment under the influence of anthropogenic load, the activity of industrial and military facilities demands the necessity for reliable assessment of the ecological condition and its forecasting in order to ensure environmental safety. This involves forecasting the further development of favorable situations or negative consequences and making adequate decisions based on the use of environmental monitoring using automated systems (decision support systems) for environmental monitoring. The main function of such systems is the complex automation of all processes related to the collection, accumulation and maintenance of various environmental registration information, in ensuring the possibility of its further processing on the basis of modern information technologies. regardless of the level of environmental monitoring, the interconnection of individual units is required: observation, information collection, assessment of the actual state of the object of observation, forecast of the future state and its assessment, management, regulation of environmental quality, for effective system operation. The use of environmental monitoring subsystems on a single geographic information basis in decision support systems will significantly reduce the time required to respond quickly to crises, which will increase the efficiency of decision-making to achieve the relevant goals and objectives. The information can be transmitted most quickly over the Internet, and the output interface should be convenient (ergonomic), not overloaded with unnecessary data and independent of the installation of specialized software. The modern full-featured geographic information platform ArcGIS allows to build not only a geographical information system of any scale and purpose, but also to form on its basis an effective system of ecological monitoring.